Enhanced Osteoinductivity of Demineralized Bone Matrix with Noggin Suppression in Polymer Matrix. Issue 1 (4th January 2021) - Chen, Chen; Rehnama, Matthew; Kim, Soyon; Lee, Chung‐Sung; Zhang, Xiao; Aghaloo, Tara; Fan, Jiabing; Lee, Min
Abstract: Demineralized bone matrix (DBM), a potential alternative to autologous bone grafts, has been increasingly used for clinical bone repair; however, its application in larger defects has not been successful partly due to the rapid dispersion of DBM particles and relatively lower osteoinductivity. Here, a novel strategy is created to complement the osteoinductivity of DBM by incorporating DBM in a biopolymer hydrogel combined with the abrogation of BMP antagonism. Combined treatment of DBM+noggin‐suppression displays increased osteogenic potency of human bone marrow mesenchymal stem cells (hBMSCs) in vitro. An injectable chitosan (MeGC)‐based hydrogel with heparinization (Hep‐MeGC) is further developed to localize and stabilize DBM. Noggin‐suppression reveals a significant increase in osteogenesis of hBMSCs in the photopolymerizable Hep‐MeGC hydrogels with the encapsulation of DBM. Moreover, the combination of DBM+noggin‐suppression in the injectable Hep‐MeGC hydrogel displays robust bone healing in mouse critical‐sized calvarial defects in vivo. The mechanistic analysis demonstrates that noggin‐suppression increases DBM osteoinductivity by stimulating endogenous BMP/Smad signals. These results have shown promise in DBM's ability as a prominent bone grafting material while being coupled with gene editing mechanism and a localizing 3D scaffold. Together, this approach poses a significant increase in the efficiency of DBM‐mediated craniofacial bone repair and dental osteointegration. Abstract : Demineralized bone matrix (DBM) is an allogeneic alternative to autografts, widely used for bone repair. The obstacle to the application of DBM is the rapid dispersion of DBM particles and relatively lower osteoinductivity. Therefore, the combined strategy is designed by incorporating DBM particles into stable polymer networks with the abrogation of BMP antagonism to improve DBM‐mediated bone regeneration.